VIDEO PROFIL RUMAH KELAHIRAN BUNG HATTA - RAYHANUL FAJRI, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
This article aims to get an innovative, communicative and efficient profile video design, with a visual display that attracts students' attention about Bung Hatta's Birthplace. Bung Hatta was one of the Indonesian Proclamation fighters born in the city of Bukittinggi, West Sumatra. Seeing the condition of Bung Hatta's Birth House is still unknown to students, managerial cooperation with the education office is needed to make students familiar with the Bung Hatta Birth House. Then one way that can be used by making attractive Profile videos and on target to inform students.This Profile video was created using the Glass Box design method with an analysis approach of 5W + 1H (what, who, when, where, why and how). This profile video is also supported with the main media, Video Profi and some supporting media such as posters, CD covers, CD labels, T-shirts, totebag, key chains, wall clocks, stickers, x-banners, mugs, pins, guest books and backdrops .Keywords: Video, Profile, Bung Hatta Birth House.